DIGITAL DARWINISM: THE SURVIVAL GAME OF AI AND ALGORITHMS - Attumkal, Mathew (Journal of Dharma, 2024)
We are currently experiencing what I would call the third phase of the Renaissance. The first phase, which began in the 15th and 16th centuries, marked a revival in science, art, literature, philosophy and religion, profoundly shaping human thought, beliefs and culture. This intellectual and scientific awakening was subsequently reinforced by the emergence of nanotechnology, particularly in the realm of scientific advancements, which pushed the boundaries of innovation. The second phase of this evolution unfolded with significant developments in psychology and environmental studies. Scholars developed a deep interest in exploring the complexities of the human mind, inspired by the works of Freud and other prominent psychologists. This period also witnessed a growing understanding of gender dynamics, fostering a greater awareness of equality and identity. Simultaneously, an increasing scientific focus on environmental preservation and the mysteries of ecosystems fueled a strong commitment to protecting nature and sustaining life on Earth, thanks to the UN declarations on Sustainable Development Goals (SDGs). Now, we have entered the third phase—an era defined by rapid technological advancements, particularly the rise of Artificial Intelligence (AI), genetic algorithms and soft computing. These innovations are transforming nearly every aspect of our lives, from healthcare and finance to education and governance. However, this technological revolution also raises a critical question: Are we witnessing a new form of survival of the fittest, where adaptability to AI-driven change determines who thrives and who is left behind?